PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DAN PENGELOLAAN KELAS TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN BISNIS RITEL KELAS XI JURUSAN BISNIS RITEL SMK NEGERI 13 MEDAN - Pasran Sitanggang; Novita Indah Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using learning media and classroom management on students’ learning interest in the retail business subject of Grade XI Retail Business Program at SMK Negeri 13 Medan. The background of this research is based on the low learning interest caused by the inadequate use of learning media and poor classroom management. The method used in this study is a quantitative method. The data collection techniques applied were giving a pretest and posttest on the use of learning media to 34 students and distributing questionnaires to 34 students to examine the effect of classroom management. Data analysis was conducted using simple linear regression with the help of SPSS version 25. The results of the study show that the use of learning media has an effect on learning interest, and classroom management also has a positive effect on students’ learning interest. Thus, the effective use of learning media can increase students’ enthusiasm for learning in class.